Export credit guarantees, moral hazard and exports quality - María del Carmen García-Alonso; Paul Levine; Antonia Morga (University of Kent, Department of Economics, 2004)
We analyse the role played by Export Credit Guarantees (ECGs) to encourage exports to developing countries. The existence of moral hazard on the side of the firm is introduced. We show that the inability of the exporter's government to verify the actual quality of the product will limit its ability to encourage trade through ECGs, once the coverage provided goes beyond a certain threshold. This result provides a rationale behind the limited coverage on ECGs.
Keywords: G12; H56; L10; 330; export credit guarantees; offsets; moral hazard; Exportgarantie; Exportkreditversicherung; Produktqualität; Moral Hazard; Theorie